The challenge of the implementation and evaluation of hospital-based cancer registry in Indonesia’s national referral hospital (Medical Journal of Indonesia, 2020)
BACKGROUND To lower the burden caused by cancer, the Ministry of Health of the republic of Indonesia requires valid data collection to plan and evaluate cancer programs. This study aimed to evaluate the challenge of developing a cancer registry (CanReg) in Cipto Mangunkusumo Hospital. METHODS This was an observational study on the implementation of cancer registration from the initial licensing until the creation of valid and accurate data, also the challenges in implementing hospital-based cancer registry (HBCR) in Cipto Mangunkusumo Hospital. RESULTS Cancer registry was developed in 2016 using the 2013 Indonesian version of CanReg5 program called SriKandI. We identified some problems in this registry implementation, such as legal and human resources, medical records, electronic health records, and the CanReg5 program. Moreover, this team processed 886,086 raw patients’ data with fairly good topography and age data completeness. CONCLUSIONS Several obstacles were encountered upon the establishment of HBCR at Cipto Mangunkusumo Hospital from program to bureaucracy and resources. Nevertheless, CanReg data can be used as a basis for decision making by stakeholders.